Efficiency of Hybrid Maize Farming at the Household Scale in Drylands - Tallo, Yohanes Fischer; Pudjiastuti, Agnes Quartina; Setiaji, Jatmiko (PT. Riset Press International, 2025)
Corn as a pillar of the household-scale farmer economy not only serves as a source of food, but also as animal feed and industrial raw material. However, the productivity of hybrid corn in the drylands of Jetak Village (4-7 tons/ha) is still much lower than in other areas (8-10 tons/ha), indicating inefficient use of inputs. This study measured technical, allocative, and economic efficiency among 96 farmers using the Cobb-Douglas production function with stratified random sampling: <0.5 ha (n=33), 0.5-1 ha (n=30), and >1 ha (n=33). NPK fertilizer consistently dominated productivity (elasticity 0.318-0.394; p<0.01) at all scales. Technical efficiency increased from 0.846 (small land) to 0.879 (large land), indicating a productivity gap of 12-15%. Economic efficiency remains suboptimal (0.619-0.688) with a potential for improvement of 31.2%. Allocative analysis shows the highest NPM/Px ratio for urea fertilizer (5.81) on large-scale land, while labor is over-utilized (NPM/Px=0.80). Contribution of the study: identification of scale-based efficiency thresholds for dryland—expansion of critical land for small farmers (NPM/Px=14.17), nitrogen intensification for medium-sized land, and labor restructuring for large land areas. Interventions should focus on NPK optimization and precision fertilization.